Answer:
a² + 2ab + b²
Explanation:
⇒ (a + b)²
⇒ (a + b)(a + b)
[apply distributive method: (a + b) (c + d) = ac + ad + bc + bd]
⇒ a² + ab + ab + b²
⇒ a² + 2ab + b²
Answer:
(a) center: (0, 0); radius: 4
(b) center: (8, -3); radius: 10
(c) center: (-2, -7); radius: 7
(d) center: (6, 0); radius: 1
(e) center: (0, 0); radius: 5
(f) center: (3, 8); radius: 8
Step-by-step explanation:
In the figure attached, the complete question is shown.
Equation of a circle with center (h, k) and radius r:
(x - h)² + (y - k)² = r²
Answer:
x=9 and y=3
Step-by-step explanation:
Let's solve your system by substitution.
−4x+6y=−18 and y=−2x+21
Rewrite equations:
y=−2x+21;−4x+6y=−18
Step: Solve y=−2x+21for y:
y=−2x+21
Step: Substitute−2x+21foryin−4x+6y=−18:
−4x+6y=−18
−4x+6(−2x+21)=−18
−16x+126=−18(Simplify both sides of the equation)
−16x+126+−126=−18+−126(Add -126 to both sides)
−16x=−144
−16x
−16
=
−144
−16
(Divide both sides by -16)
x=9
Step: Substitute9forxiny=−2x+21:
y=−2x+21
y=(−2)(9)+21
y=3(Simplify both sides of the equation)
Answer:
x=9 and y=3